(untitled) (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2015)
Ten years ago, the Speech Therapy program at the University of Pamplona welcomed its first students, 55 young people who embraced a training approach that was novel for many, yet strange for others. A path that those who decided to pursue to the end loved, defended, and helped to build. Today, the scientific journal Signos Fónicos emerges as the realization of this dream, with 52% of articles in its first edition covering the topics of Orofacial Motor Skills, Dysphagia, and Speech, the majority of which correspond to works developed by faculty, graduates, and students of the Speech Therapy program at the University of Pamplona. In this sense, it is clear that the goals set since 2005 have been met over time.